THE MENTAL HEALTH OF FIRST- AND FINAL-YEAR PRECLINICAL MEDICAL STUDENTS - Michelle Stephanie; Charles Surjadi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: Medical students consistently have higher rates of mental health problems, these include higher levels of stress, anxiety, and burnout, alongside low levels of overall health, and energy. The study aimed to determine the prevalence and the factors influencing the mental health of first- and final-year preclinical students in Unika Atma Jaya.Methods: A cross-sectional study was conducted on all first-year preclinical students (196 respondents) and all final-year preclinical students (115 respondents) using Self Reporting Questionnaire (SRQ). Data were then analyzed using Mann-Whitney U test, chi square, and Fisher’s exact test.Results: 95 out of 196 (48.5%) of first-year students and 22 out of 115 (19.1%) of final-year students have SRQ score of ³6. Mental health of first-year students were found to be related to their religion and personal life events. Meanwhile factors affecting the mental health of final-year students were their motivation in enrolling to medical school and personal life events.Conclusion: There is a significant difference of mental health in first- and final-year students (48.5% and 19.1%). This may be related to their religion, personal life events, and their motivation in enrolling to medical school. Keywords: mental health, medical students, self reporting questionnaire